Role of neurosurgeons In strengthening paediatric neuro-oncology In low- and middle-income countries: a narrative review with case examples - Ahsan Ali Khan; Mohammad Hamza Bajwa; Naureen Mushtaq; Muhammad Osama; Afia Arif; Saqib Kamran Bakhshi; Michael C. Dewan; Kee B Park; Eric Bouffet; Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Paediatric neuro-oncology in low- and middle-income countries (LMICs) accounts for a significant proportion of cancer-related mortalities in this age group. The current dearth of structured paediatric neurosurgery training programmes in LMICs requires multidisciplinary coordination; neurosurgeons play certain key roles, as discussed in this article, in ensuring safe and effective care for paediatric neuro-oncology patients. This document intends to elaborate through illustrative cases of the technical and structural nuances required by neurosurgeons in LMICs to provide appropriate surgical care. Keywords: Neuro-oncology, neurosurgery, Neoplasms